2021
DOI: 10.1021/acs.jafc.0c07831
|View full text |Cite
|
Sign up to set email alerts
|

Tripeptide IRW Upregulates NAMPT Protein Levels in Cells and Obese C57BL/6J Mice

Abstract: Nicotinamide adenine dinucleotide (NAD+) plays a vital role in cellular processes that govern human health and disease. Nicotinamide phosphoribosyltransferase (NAMPT) is a rate-limiting enzyme in NAD+ biosynthesis. Thus, boosting NAD+ level via an increase in NAMPT levels is an attractive approach for countering the effects of aging and metabolic disease. This study aimed to establish IRW (Ile-Arg-Trp), a small tripeptide derived from ovotransferrin, as a booster of NAMPT levels. Treatment of muscle (L6) cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…These cell lysates were run on SDS-PAGE, transferred to nitrocellulose membranes, and immunoblotted with primary antibodies according to the recommended concentration(s) by manufacturer. After incubating with the secondary antibodies, protein bands were detected using a Licor Odyssey BioImager (Licor Biosciences, Lincoln, NB) and quantified by densitometry using Image Studio Lite 5.2 software, as described in our recent report ( Bhullar et al, 2021a ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These cell lysates were run on SDS-PAGE, transferred to nitrocellulose membranes, and immunoblotted with primary antibodies according to the recommended concentration(s) by manufacturer. After incubating with the secondary antibodies, protein bands were detected using a Licor Odyssey BioImager (Licor Biosciences, Lincoln, NB) and quantified by densitometry using Image Studio Lite 5.2 software, as described in our recent report ( Bhullar et al, 2021a ).…”
Section: Methodsmentioning
confidence: 99%
“…First, the mitochondria were extracted from the cells as per our recent report ( Bhullar et al, 2021a ). Next, according to a previous report, DNA extraction was conducted ( Boccellino et al, 2003 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our team focused on adding this active peptide to the host diet, exploring the prevention and treatment of intestinal damage. We explored the impact of colitis by adding IRW and IQW to the diet of a DSS-induced colitis mouse model; research showed that IQW could adjust the amino acid levels in serum and regulate intestinal immune function to relieve inflammation; IQW and IRW could reduce oxidative stress induced by DSS by increasing antioxidant enzyme activity; IQW and IRW achieved this by increasing the diversity of the host's intestinal microorganisms and increasing the probiotic biomass [16,17]. In view of the IQW and IRW effect in the DSS-induced mouse model, we expect IQW and IRW can perform a similar effect in the ETECinduced mouse model.…”
Section: Introductionmentioning
confidence: 99%